An alternative approach to evidence the structural conditioning in the dynamic slowdown in a polymer glass-former - Balbuena, Cristian (2019)
Dynamic slowdown of liquids, leading to a breakdown of Arrhenius behavior of relaxation and Stokes-Einstein relationship (SER), as the glass transition is approached, is still not fully understood despite decades of study. They are usually associated to the emergence of dynamic heterogeneity, that is, regions or clusters of particles that have high or low mobilities. But the physical origin of these dynamic heterogeneity, and in particular, the question whether they have a structural origin or they are a purely dynamical phenomenon, is still under debate. In this work we study through molecular dynamics simulations in a polymer model the dynamic slowdown and the breakdown of SER, in connection with dynamic susceptibility calculated for an isoconfigurational ensemble, such that the effects of structure on dynamics can be discriminated. The onset of structure effects on dynamical behavior is found to be coincident with the onset of slow dynamics and SER breakdown.